2017
DOI: 10.1038/s41467-017-00448-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered red cells expressing single domain camelid antibodies confer long-term protection against botulinum neurotoxin

Abstract: A short half-life in the circulation limits the application of therapeutics such as single-domain antibodies (VHHs). We utilize red blood cells to prolong the circulatory half-life of VHHs. Here we present VHHs against botulinum neurotoxin A (BoNT/A) on the surface of red blood cells by expressing chimeric proteins of VHHs with Glycophorin A or Kell. Mice whose red blood cells carry the chimeric proteins exhibit resistance to 10,000 times the lethal dose (LD50) of BoNT/A, and transfusion of these red blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 48 publications
1
61
0
Order By: Relevance
“…Enriched erythroid progenitors were purified from embryonic day 14.5 (E14.5) C57BL/6J mouse embryos, and cultured in vitro for erythroid differentiation following a protocol described in detail previously. 6 Briefly, pregnant C57BL/6J mice at E14.5 were sacrificed by CO 2 asphyxiation and their embryos were collected. The fetal livers were isolated and suspended in PBS with 2% FBS and 100 mM EDTA.…”
Section: Isolation Of Erythroid Progenitors From Murine Fetal Liver Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Enriched erythroid progenitors were purified from embryonic day 14.5 (E14.5) C57BL/6J mouse embryos, and cultured in vitro for erythroid differentiation following a protocol described in detail previously. 6 Briefly, pregnant C57BL/6J mice at E14.5 were sacrificed by CO 2 asphyxiation and their embryos were collected. The fetal livers were isolated and suspended in PBS with 2% FBS and 100 mM EDTA.…”
Section: Isolation Of Erythroid Progenitors From Murine Fetal Liver Cmentioning
confidence: 99%
“…To strengthen our findings, we studied aspects of metabolism during the 23-day period of differentiation in vitro of human mobilized bone marrow CD34 1 stem/progenitor cells into enucleated erythrocytes. 6 The culture system comprises 5 stages and differentiation is highly synchronized. We analyzed metabolites from cells at the end of each of the differentiation stages (Diff1-Diff5).…”
Section: Phospho1 Depletion Impairs Human Erythropoiesismentioning
confidence: 99%
“…38,39 Large-scale synchronized axenic culture system based on peripheral CD34 + HSPCs has the highest yield and enucleation rate reported so far. 13 The entire erythroid culture consists of an expansion of HSPCs, followed by 5 differentiation phases with varying cell density, cytokines and growth factors resulting in a 14 700-fold expansion over 23 days ( Fig. S1, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro erythroid cultures of reticulocytes have progressed significantly achieving more than 60% purity with >300 000 fold expansion. 13 However, this process requires erythroblasts, to eject their nuclei resulting in a viscous culture medium due to the accumulation of the expelled nuclei contaminants. 6 Downstream applications such as cellfree protein translation, RBCs production and malaria invasion of reticulocytes require purified reticulocytes free from extra-cellular DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Bakherad et al [ 26 ] reported a VHH that neutralized BoNT/E and partially protected against intoxication in mice. VHH-based neutralizing agents (VNAs) consisting of two linked neutralizing VHH components have proven highly effective in protecting mice from BoNT/A and BoNT/B intoxication when administered as proteins [ 21 , 25 ], on red blood cells [ 27 ], or by gene therapy [ 12 , 20 ], offering novel therapeutic options for botulism.…”
Section: Introductionmentioning
confidence: 99%